2018
DOI: 10.2147/ijn.s168998
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of wound healing using bioinspired hydrogels with basic fibroblast growth factor (bFGF)

Abstract: IntroductionThe objective of this study is to stimulate wound healing using bioinspired hydrogels with basic fibroblast growth factor (bFGF).Materials and methodsInspired by the crosslinking mechanism in algae-based adhesives, hydrogels were fabricated with gum arabic, pectin, and Ca2+. The physical properties of the bioinspired hydrogels were characterized, and the in vitro release of bFGF was investigated. Then, the in vitro scratch assay for wound healing and in vivo wound healing experiment in a full-thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 47 publications
(49 reference statements)
1
101
0
4
Order By: Relevance
“…A bioactive hydrogel may be able to stimulate cell migration 18 , proliferation 19 , and differentiation 20 , and enhance blood vessel formation during the woundhealing process 21 , so that the hydrogel can significantly reduce the healing time [21][22][23] . Currently, hydrogels with bioactivity are mainly obtained by the addition of growth factors 24 , which still faces challenges in clinical applications, such as their controlled delivery and activity maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…A bioactive hydrogel may be able to stimulate cell migration 18 , proliferation 19 , and differentiation 20 , and enhance blood vessel formation during the woundhealing process 21 , so that the hydrogel can significantly reduce the healing time [21][22][23] . Currently, hydrogels with bioactivity are mainly obtained by the addition of growth factors 24 , which still faces challenges in clinical applications, such as their controlled delivery and activity maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor (FGF)-2 and vascular endothelial growth factor (VEGF) have been determined to promote angiogenesis synergistically, and therefore, have much caution in the field of wound healing [27]. It has been reported that topical administration of FGF-2 could enhance cell proliferation and migration, wound reepithelialization and collagen deposition [28,29]. In an animal model of surgically wounded submandibular glands, the use of collagen gels with FGF-2 improved salivary gland regeneration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Bis heute ist also die Effizienz von B-FGF bezüglich der Wundheilung unklar -weitere Studien mit einer größeren Patientenzahl fehlen. Zusätzlich können spezielle Hydrogels oder Co-Faktoren die Effizienz von B-FGF signifikant steigern [69,70].…”
Section: Mscs Für Die Wundheilungunclassified